(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
This research is motivated by the fact that there are still students who do not display a religious character in implementing tahfidz Al-Qur’an at SMPN 3 Sungai Pua. This research aims to determine the implementation of extracurricular tahfidz Alquran students at SMPN 3 Sungai Pua, determine the implementation of the religious character of students at SMPN 3 Sungai Pua, and determine the influence of extracurricular tahfiz Alquran on the religious character of students at SMPN 3 Sungai Pua. This research uses quantitative methods with a correlational approach. Data was taken from 32 respondents using total sampling technique. Data collection was carried out through tahfidz tests and questionnaires. Then the data was analyzed using SPSS 26 for Windows. The research results show i). based on descriptive data on the implementation of extracurricular tahfiz Alquran and the religious character of students at SMPN 3 Sungai Pua is in the medium category, ii) there is a significant influence between extracurricular tahfiz Alquran on the religious character of students at SMPN 3 Sungai Pua, significance value is 0.000<0.005. The influence of extracurricular tahfiz Alquran on religious character was 41.3% while the remaining 58.7% was influenced by other factors that could not be examined in this study. The results of this research can be used as initial data for future researchers in studying problems in different issue contexts.